Representasi Pesan Mental Health Pada Lagu “Tutur Batin” dan “Jalan Pulang” Karya Yura Yunita - Ardita, Rina; Wirawanda, Yudha (Unitri Press, 2024)
Music can be something that helps someone to maintain mental health because music videos and lyrics can motivate such as the songs entitled